A Importância da formação continuada em tecnologias digitais e recursos audiovisuais para o ensino de língua inglesa - Andrade, Antonio da Silva (2021)
The objective of this research is to verify if the teachers have any continuing education that considers the work with digital technologies and audiovisual resources in the teaching of English Language. The study also aims to discuss how much the teacher needs to be trained to be able to work profitably with digital technologies and audiovisual resources in the classroom. As for the methodological procedures, it is a quantitative-qualitative exploratory research through a field research, seeking to show evidence on the use and training of teachers in digital technologies and audiovisual resources in English language teaching. Data were presented in frames, with simple statistical treatment. The results showed that there is a great lack of training for teachers in digital technologies and audiovisual resources in education and that teachers, even with little preparation, use various technologies to teach the English language. The analyzed results demonstrate that the effective use of digital technologies in the classroom improves the development of English language learning. In this research, we conceptualized digital technologies from the theoretical conceptions of Moran (1995), Moreira and Kramer (2007), Neto (1982) and Thompson (1998).